Analisis Semiotika Roland Barthes pada Film “Ranah 3 Warna” Karya Guntur Soeharjo - Siti Khofifah (Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study aims to analyze Guntur Soeharjo's film Ranah 3 Warna through the perspective of Roland Barthes' semiotic theory. As one of the leading semiotic theorists, Barthes offers an approach that can uncover hidden meanings in visual texts, such as films. In this context, the film Ranah 3 Warna, adapted from a novel by Ahmad Fuadi, depicts the life journey of a young man who faces various challenges in his personal life, family, and society. This analysis uses Barthes's main concepts, such as denotation, connotation, and myth, to identify how the visual and narrative elements in the film form deeper meanings. This study reveals that through the signs and symbols in the film, social, cultural messages and values form certain myths in Indonesian society. The results of this study are expected to enrich the understanding of the application of semiotic theory in film analysis and show how the film Ranah 3 Warna can reflect complex social realities through the visual language and narrative developed.